Characterisation of microstructure evolution during creep of P91 steel using the electron backscatter diffraction technique. (4th May 2021) - Zhang, Kai; Liu, Xinbao; Zhu, Lin
ABSTRACT: The present work deals with the microstructure evolution during creep of P91 steel. In particular, the changes of prior austenite grain (PAG) and low-angle grain boundary (LAGB) during creep were studied using the electron backscatter diffraction (EBSD). Firstly, a series of crept specimens of P91 steel were prepared at 893 K under a constant stress of 145 MPa. Then, the EBSD measurements of these specimens were carried out. Subsequently, the PAGs were reconstructed successfully with the measured EBSD data, and the resultant distribution of LAGBs was calculated. Consequently, the obtained results suggested that the size of PAGs has not changed significantly during the whole creep. For the distribution of LAGBs, however, the peak shifted obviously to high angles during creep. In addition, it demonstrated that the EBSD method offers an effective and quantitative tool to characterise the microstructure evolution during creep of P91 steel.